Myxobolus sp. (Myxozoa) in the circulating blood of Colossoma macropomum (Osteichthyes, Characidae) - Maciel,Patricia Oliveira (2011)
Myxosporea parasitize many organs in fresh and saltwater fish. Species of the genus Myxobolus parasitizing the gills and other organs of the tambaqui Colossoma macropomum have been described. In the present study, blood smears were made from juvenile tambaqui and were stained with May Grunwald-Giemsa-Wright in order to identify myxozoan parasites. Out of a total of 36 fish examined, one specimen (2.7%) that was reared in a cage presented spores that were identified as M. colossomatis, whereas fish kept in 250 L tanks showed prevalence of 5.5%. This is the first report of M. colossomatis in the blood of farmed tambaqui in the Amazon region. These results indicate that myxozoan parasites should also be investigated in fish blood smears. Some myxosporean species may cause diseases in fish, and these species need to be identified so that adequate preventive sanitary control can be instituted.